SISTEM PENGAMAN TEGANGAN LEBIH PADA JARINGAN TEGANGAN MENENGAH 20kV-ARUS BOLAK-BALIK (AC) TERHADAP PETIR - Syarifil anwar (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2018)
Electric power system can be broadly divided into three sub-systems, namely generation system, Transmission system and distribution system.The distribution system can also be called the medium voltage network or called the primary distribution system using 20kV. Distribution system, the network is widely spread in densely populated areas, buildings, and others, so many have disturbances, both from outside the system (external system) and from within the system it self (internal system). In order for electrical energy to be channeled to the consumer running smoothly and well and trustworthy, then the Disorders should be reduced even to be eliminated. Therefore a medium-voltage 20kV network must be secured from all interference. Disturbance in the most dangerous 20kV intermediate voltage network is over voltage disturbance caused by lightning strikes, either direct or indirect strokes, and therefore must be secured by a device called Ground Wire and Arrester. Keyword: Medium Voltage 20kV-AC, Lightning Phenomenon, Over Voltage Device